Genome-wide Studies of knee Osteoarthritis: Review - Vitaly B. Novakov (Travmatologiâ i Ortopediâ Rossii, 2021)
Background. Knee osteoarthritis (OA) is a multifactorial disease resulting from the interaction of many environmental, epigenetic and genetic risk factors, and the latter account for 40% to 65%. Genetic bases of the knee OA based on genome-wide association study (GWAS) are being actively studied by many scientific teams around the world. At the same time, the results obtained are often contradictory and ambiguous, as for the conducted replicative studies of knee OA. This dictates the need for additional replicative studies in various populations, including populations of Russia. The aim of the study was to analyze genome-wide studies of knee OA and to establish GWAS-significant polymorphic loci associated with OA. Materials and Methods. The search for publications was carried out in the electronic databases PubMed, PubMedCentral, eLIBRARY, in the GWAS catalog for the period from 2008 to the present by the keywords: knee osteoarthritis, GWAS studies, candidate genes. Results. Firstly, for the period from 2008 to 2021, 15 genome-wide studies of knee OA were performed (8 GWAS, 6 meta-analyzes of GWAS data, 1 study a combination of GWAS and meta-analysis of GWAS data), as a result of which 78 polymorphic loci were found associated with the risk of developing osteoarthritis of the knee joint at p510-08. Second ly, the vast majority of these loci (62 out of 78 SNPs, 79%) showed GWAS-significant associations with OA in meta-analyzes of GWAS data and only 16 loci (21%) in GWAS studies. Third ly, almost 95% of GWAS-significant loci for knee OA (74 SNPs) were found in samples of Caucasian origin. Fourthly, 21 out of 78 GWAS-significant SNPs are associated with isolated knee OA, and 57 SNPs are associated with knee, hip and hand OA (mixed sample). Fifth, all genome-wide studies of knee OA and meta-analyzes of GWAS data were carried out abroad on samples from various foreign populations, and samples from the Russian Federation were not included in these studies. Sixth, only two GWAS-significant polymorphic loci for OA (rs143384 of the GDF5 gene for knee OA isolated localization and rs3771501 of the TGFA gene for OA of any localization) were replicated at the whole genome level of significance (p510-08) in two different studies. Conclusion. The main genome-wide studies of knee OA were reviewed and GWAS-significant polymorphisms associated with OA were identified. The obtained materials on GWAS-significant loci can be used both in the selection of polymorphisms in replicative studies of OA in various populations of Russia, and for expanding the understanding of the molecular genetic mechanisms of the disease development.